2009
DOI: 10.1111/j.1468-2982.2008.01707.x
|View full text |Cite
|
Sign up to set email alerts
|

Ictal Headache and Visual Sensitivity

Abstract: Migrainous headache is reported by patients with photosensitive epilepsy, whereas their relatives complain more often about headache than the relatives of patients with other types of epilepsy. We therefore investigated whether headache itself could be an epileptic symptom related to photosensitivity. Four probands with headache and photosensitive epilepsy were selected. Their first-degree family members were studied using video-EEG with extensive intermittent photic stimulation and pattern stimulation. Nine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 29 publications
(36 reference statements)
4
66
0
Order By: Relevance
“…mainly a peri-ictal phenomenon), but in some cases (whose number is probably largely underestimated) "the headache represents the only ictal phenomenon": we recently named this condition "ictal epileptic headache" (Parisi et al 2012a). Since 1971, fewer than 20 IEH cases diagnosed according to proposed criteria (Table 1, Parisi et al 2012b) have been reported (Grossman et al 1971;Walser and Isler 1982;Laplante et al 1983;Isler et al 1987;Niedermeyer 1993;Marks and Ehrenberg 1993;Walker et al 1995;Ghofrani et al 2006;Parisi et al 2007;Piccioli et al 2009;Perucca et al 2010;Belcastro et al 2011c;Fusco et al 2011;Italiano et al 2011;Fanella et al 2012;Cianchetti et al 2013). Verrotti et al recently published 16 other potential ictal epileptic headache cases from a large multicentre neuropediatric sample (Verrotti et al 2011b), stressing the concept of "probable underestimate phenomenon" (Parisi et al 2012a;Parisi et al 2013a, b).…”
Section: Sunset Of the "Migralepsy" Conceptmentioning
confidence: 96%
See 3 more Smart Citations
“…mainly a peri-ictal phenomenon), but in some cases (whose number is probably largely underestimated) "the headache represents the only ictal phenomenon": we recently named this condition "ictal epileptic headache" (Parisi et al 2012a). Since 1971, fewer than 20 IEH cases diagnosed according to proposed criteria (Table 1, Parisi et al 2012b) have been reported (Grossman et al 1971;Walser and Isler 1982;Laplante et al 1983;Isler et al 1987;Niedermeyer 1993;Marks and Ehrenberg 1993;Walker et al 1995;Ghofrani et al 2006;Parisi et al 2007;Piccioli et al 2009;Perucca et al 2010;Belcastro et al 2011c;Fusco et al 2011;Italiano et al 2011;Fanella et al 2012;Cianchetti et al 2013). Verrotti et al recently published 16 other potential ictal epileptic headache cases from a large multicentre neuropediatric sample (Verrotti et al 2011b), stressing the concept of "probable underestimate phenomenon" (Parisi et al 2012a;Parisi et al 2013a, b).…”
Section: Sunset Of the "Migralepsy" Conceptmentioning
confidence: 96%
“…Following the introduction of the migralepsy concept by Lennox and Lennox (1960), an increasing number of ictal epileptic headaches have been reported since the 1970s (Grossman et al 1971;Walser and Isler 1982;Laplante et al 1983;Isler et al 1987;Niedermeyer 1993;Marks and Ehrenberg 1993;Walker et al 1995;Ghofrani et al 2006;Parisi et al 2007;Piccioli et al 2009;Perucca et al 2010;Belcastro et al 2011c;Fusco et al 2011;Italiano et al 2011;Fanella et al 2012;Cianchetti et al 2013). It has also been suggested (Parisi and Kasteleijn-Nolst Trenité 2010;Belcastro et al 2011a;Verrotti et al 2011a, b;Striano et al 2011Striano et al , 2012Parisi et al 2012aParisi et al , 2013a that the migralepsy sequence may not exist at all and that the initial part of the "migralepsy sequence" may merely be an "ictal epileptic headache" (Parisi et al 2012a) followed by other ictal autonomic, sensory, motor or psychic features.…”
Section: Sunset Of the "Migralepsy" Conceptmentioning
confidence: 96%
See 2 more Smart Citations
“…Ictal headaches are reported by less than 5% of patients with epilepsy [20], and in some patients it might reflect a true epileptic phenomenon [21]. The relatively low prevalence of ictal headaches might be a consequence of cognitive or consciousness impairments provoked by seizures.…”
Section: Ictal Headachesmentioning
confidence: 99%